Impact of coal power production on sustainable water resources management in the coal-fired power energy bases of Northern China. (15th September 2019) - Gao, Xuerui; Zhao, Yong; Lu, Shibao; Chen, Qianyun; An, Tingli; Han, Xinxueqi; Zhuo, La
Graphical abstract: Highlights: Water is scarce in the nine coal-fired energy bases of the north and west China. The water footprint of coal and power production in the nine bases is evaluated. The virtual water flow along with the energy products transfer is also analyzed. Water stress in the energy bases is keeping increasing in the past and future. The comprehensive countermeasures are proposed to ensure water and energy security. Abstract: In the past decades, the nine major energy bases in north and west China produced increasing amounts of coal and coal-fired power to meet rapidly growing energy demand. However, the poor water resources condition has become a bottleneck for sustainable development. In this study, the water footprint of coal and power production is evaluated, and the flow of virtual water arising from the transport of energy products is quantified. The results show that total coal and power production increased continuously from 2006 to 2015. The annual total water footprint was as much as 1.29 billion m 3 ; it showed an initially increasing trend that peaked in 2013, after which it decreased. After 2013, the water footprint decreased primarily as a result of improvements in water-saving technologies. The results also indicate that increasing amounts of virtual water (as much as 0.87 billion m 3 in 2015) embedded in energy products flowed from the north and west water deficient areas to the southeast water-rich areas of China, causing severe water scarcity in the major energy producing regions. Unfortunately, based on our estimates, water stress will continuously increase during the 13th Five-Year Plan period (2016–2020). This study finds that water-saving measures alone are not sufficient to relieve the water shortage and to guarantee water security. Comprehensive countermeasures, including an adjustment to the industrial structure, the physical transfer of water, regulation of the virtual water trade and policy and planning changes, are also necessary.